The Effect of Teaching Technologies Used in Theories of Architecture Lectures in Students’ Performance - Rana Mahfooth; Niam. B. Mannona; Ali H. Al-Jameel (Iraqi Journal of Architecture and Planning)
"Recently, educational technologies have become an important issue thanks to the vast developments in the fields of information and digital technologies as new means were introduced to become essential parts of teaching methods. Because of their role in promoting education in general and the architectural education specifically, as they are new means for introducing knowledge in the theoretical lectures to accelerate the process of learning, it seems essential to provides scientific knowledge about their efficiency intended educational goals. On the other hand, Theories of Architecture is one of the principal lectures in architectural schools as the knowledge introduced in them is highly relevant for learning the design process within the lectures of Architectural Design. This research adopts the goal of testing the hypothesis of the effect of teaching technologies used in Theories of Architecture lectures in promoting students’ performance by employing an experimental method within which the students of the fourth year in the department of Architectural Engineering in Mosul University were subjected to an experiment within specific theoretical framework. It is concluded that specific teaching technologies are more convenient for certain objectives and the instructor should employ different teaching technologies with integrative approach for more efficient Architectural Education to be achieved."